2021
DOI: 10.1021/acsanm.0c02896
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Studies of Doping and Curvature Effects on the Electrocatalytic Hydrogen Evolution Activity of Carbon Nanotubes

Abstract: Using low-cost, efficient, and stable nonprecious alternatives for Pt-based catalysts is important for electrocatalytic hydrogen evolution reaction (HER), and carbon nanotubes (CNTs) with atom doping have shown great potential in electrocatalytic HER. In this work, we have systematically investigated the HER catalytic activities for a series of different curvature CNT (n,n) (n = 5–9), doped with atomic N or N and Co via the first-principle computation. The computed results indicate that H binding capability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Recently, it was also shown that different curvatures of N‐doped CNTs could also increase the HER activity of the CNTs as increasing the curvature increased the H binding ability of both pure and doped CNTs. [ 535 ]…”
Section: Electrocatalytic Hydrogen Evolution Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was also shown that different curvatures of N‐doped CNTs could also increase the HER activity of the CNTs as increasing the curvature increased the H binding ability of both pure and doped CNTs. [ 535 ]…”
Section: Electrocatalytic Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Recently, it was also shown that different curvatures of N-doped CNTs could also increase the HER activity of the CNTs as increasing the curvature increased the H binding ability of both pure and doped CNTs. [535] 6.4. Fullerene-Based Electrocatalytic HER Fullerenes possess unique chemical and physical properties with their spherical cage and hollow interior structure that have been exploited in a wide variety of applications.…”
Section: Theoretical Calculations Of Doped and Defected Cnts For Hermentioning
confidence: 99%
“…Recent experimental and theoretical studies have both indicated that the active sites of such MN 4 -based SACs are centralized at the metal single-atoms attached to four pyridine nitrogen atoms anchored in the extended carbon matrix. To directly probe the atomic and electronic structures of these catalytic sites in different curvature environments, the carbon matrices are represented in this work by a series of single-walled carbon nanotubes (SWNTs) of various diameters, 22,35,36 as illustrated in Fig. 1.…”
Section: Structural Features Of Curved Mn 4 -Based Sacsmentioning
confidence: 99%
“…T Δ S H is the entropic contribution of H*, which is equal to 0.203 eV under standard conditions ( T = 298 K and P = 1 bar) in this calculation. Δ E H* is the adsorption energy of a single H atom, which can be calculated as the following equation: 43,44 …”
Section: Computational Detailsmentioning
confidence: 99%
“…The exchange current density ( i 0 ) at pH = 0 can be defined as: 43,44 where the rate constant k 0 is set to be 1 and k B is the Boltzmann constant.…”
Section: Computational Detailsmentioning
confidence: 99%